2020
DOI: 10.1186/s40463-020-00428-3
|View full text |Cite
|
Sign up to set email alerts
|

Simple hypertrophic tonsils have more active innate immune and inflammatory responses than hypertrophic tonsils with recurrent inflammation in children

Abstract: Background: Tonsil hypertrophy has negative impact on children's health, but its pathogenesis remains obscure despite the fact that numerous bacteriological studies have been carried out. Understanding the innate immune and inflammatory states of hypertrophic tonsils with different clinical manifestations is of great significance for defining the pathogenesis of tonsil hypertrophy and establishing treatment strategies. The present study was undertaken to examine the characteristics of innate immunity and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Large tonsils in adulthood may be more immunologically functional than small tonsils. This notion is in line with a recent study conducted in children [34], although the phenomenon is far from being explored satisfactorily. However, as mentioned above, the hypertrophic tonsils may also be indicators of increased susceptibility to infections, and it could be these infections which may lead both to tonsillectomy and progress to various cancers [3,5], especially when the tonsils are removed.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Large tonsils in adulthood may be more immunologically functional than small tonsils. This notion is in line with a recent study conducted in children [34], although the phenomenon is far from being explored satisfactorily. However, as mentioned above, the hypertrophic tonsils may also be indicators of increased susceptibility to infections, and it could be these infections which may lead both to tonsillectomy and progress to various cancers [3,5], especially when the tonsils are removed.…”
supporting
confidence: 88%
“…Retinoic acid–inducible gene I (RIG-I), interferon alpha (IFN-α), mitochondrial antiviral-signaling protein (MAVS), NLR family pyrin domain containing 3 (NLRP3), toll-like receptor (TLR) 4 and TLR7, and several inflammatory markers (such as IL-1β, NF-κB, and IL-7) have been shown to be highly expressed in simple hypertrophic tonsils (i.e. not in hypertrophic tonsils with recurrent tonsillitis), showing the activity of pathogen-induced innate immune responses [ 34 ]. Likewise, neutrophil–lymphocyte ratio (NLR), lymphocyte-monocyte ratio (LMR), platelet-lymphocyte ratio (PLR), and mean platelet volume (MPV) have been determined as indicators of systemic inflammation in adults [e.g.…”
mentioning
confidence: 99%
“…IL-10) in both these conditions. Huang et al [39] found IL-1 and IL-10 in the hypertrophic palatine tonsil tissue as well as in hypertrophy with coexisting tonsillitis. The researchers demonstrated higher expression levels of the tested cytokines in the group with isolated hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recurrent infections of the respiratory tract and allergic/atopic diseases contribute to pathologies, such as adenotonsillar hypertrophy and chronic middle ear effusions that may necessitate surgical management. 7–10 The causative pathogens and allergens are extremely widely distributed, but only a minority of children require otolaryngology surgery. Shared heritable and postnatal environmental factors, such as cigarette smoke, contribute modestly to differential risk.…”
mentioning
confidence: 99%